2011
DOI: 10.1016/j.pedneo.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Renal Calcification in Very Low Birth Weight Infants

Abstract: The incidence of renal calcification in very low birth weight infants in this study was relatively low, and the calcification was transient in one-half of the infants. Extremely premature, sick infants requiring long-term ventilation, and those receiving furosemide or dexamethasone were more likely to have renal calcification. Clinicians should be aware that renal calcification may develop beyond the neonatal stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…[3][4][5][6][7][8][9] The varying prevalence of NC is considered to be due different study populations and era, development in the sensitivity of ultrasound equipment, and workmanship of the observer. 27 In several reports, the incidence of NC showed a decreasing trend with development in care of preterm infants, 6,20,24 but this study showed an increasing tendency for NC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9] The varying prevalence of NC is considered to be due different study populations and era, development in the sensitivity of ultrasound equipment, and workmanship of the observer. 27 In several reports, the incidence of NC showed a decreasing trend with development in care of preterm infants, 6,20,24 but this study showed an increasing tendency for NC.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] At a low gestational age, the lower glomerular filtration ratio and the shorter loop of Henle lead to slow urinary transition, while the sensitivity for heterogeneous crystallization is high, which result in decreased calcium excretion and increased calcification. Also, during the neonatal period, VLBW infants are exposed more frequently and for a longer time to multiple risk factors associated with treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to furosemide more than 10 mg/kg body weight cumulative dose has recently been shown by multivariate analysis to be the strongest independent risk factor for nephrocalcinosis (Chang, Hsu & Tsai, 2011).…”
Section: Steroids and Diureticsmentioning
confidence: 99%
“…In addition, the half-life is further increased in premature infants, with a halflife that is 6 hours in term infants and as long as 67 hours in premature infants [16]. However, increased knowledge of the pharmacokinetics and complications of using loop diuretics in infants have decreased the incidence of stones associated with these drugs [17,18].…”
Section: Introductionmentioning
confidence: 99%